Childhood Behavioral Patterns and Professional Character Formation of High-Achieving RA Teachers - Noor, Fu'ad Arif; Nasucha, Zubaedah; Kurniasari, Nia (THUFULA, 2025)
This research analyzes behavioral patterns of high-achieving Raudhatul Athfal (RA)  teachers in Yogyakarta during their golden age and their impact on professional exemplary behavior. Qualitative research with interpretative psychological approach involved five RA teachers who won the 2017 provincial competition. Data were collected through moderate participatory observation, in-depth interviews, and documentation, then analyzed using interactive models with source, technique, and time triangulation. Most subjects lacked formal kindergarten education yet demonstrated superior learning creativity. Four dominant patterns emerged: early independence, physical-mental resilience, spiritual discipline, and natural leadership. Diverse parenting styles (permissive, participative, religious authoritarian, democratic) with value consistency produced high resilience and adaptability. Natural play experiences—playing in rain, helping in rice fields, extensive socialization—became foundations of professional excellence. These childhood experiences directly influenced their innovative teaching methods, strong work ethic, and ability to form meaningful relationships with students and colleagues. Golden age experiences consistently shape RA teachers' exemplary character and professional competence. Findings suggest the necessity for holistic teacher development approaches that consider developmental history alongside formal academic qualifications, potentially revolutionizing early childhood teacher education programs.